Crystal structure of catena-poly[[chlorido(4,4′-dimethyl-2,2′-bipyridine-κ(2) N,N′)copper(II)]-μ-chlorido] - Nita, Rafaela (Acta Crystallogr E Crystallogr Commun, 2015)
The title compound, [CuCl(2)(C(12)H(12)N(2))](n), was obtained via a DMSO-mediated dehydration of Cu(4,4′-dimethyl-2,2′-bipyridine)copper(II)·0.25H(2)O. The central Cu(II) atom is coordinated in a distorted trigonal–bipyramidal geometry by two N atoms of a chelating 4,4′-dimethyl-2,2′-bipyridine ligand [average Cu—N = 2.03 (3) Å] and three Cl atoms, one terminal with a short Cu—Cl bond of 2.2506 (10) Å, and two symmetry-equivalent and bridging bonds. The bridging Cl atom links the Cu(II) ions into chains parallel to [001] via one medium and one long Cu—Cl bond [2.3320 (10) and 2.5623 (9) Å]. The structure displays both inter- and intramolecular C—H⋯Cl hydrogen bonding.